ИНТЕГРАЛ ГЕОМЕТРИЯДА БИР МӘСЕЛЕНИҢ ПАРАБОЛАЛАР СЕМЬЯСЫНДАҒЫ ОРНЫҚЛЫЛЫҒЫ - Утеулиев, Н.У.; Сеидуллаев, А.К.; Даниярова, Г.К. (FAN va JAMIYAT, 2023)
This article proves the stability of the solution to a special weight function of a problem belonging to the family of parabolas of integral geometry problems.